Irrigation and Debridement for Periprosthetic Hip Infection: Does Timing Play a Role? - Sayeed, Yousuf; Quien, Mary; Anoushiravani, Afshin A.; Kim, Kelvin Y.; Camus, Tristan; Schwarzkopf, Ran; Adler, Edward (The Journal of Hip Surgery, 2017)
Periprosthetic joint infection (PJI) is a devastating complication of total joint arthroplasty (TJA). The rate of PJIs in total hip arthroplasty (THA) procedures varies from 0.3 to 2.9%. Irrigation and debridement (I&D) with modular implant exchange is often performed to treat PJIs. Early management of infection is cited to offer a higher success rate. The goal of this study was to examine the outcomes of early I&D for THA PJIs. We reviewed 38 patients diagnosed with a PJI between 2009 and 2014 who went on to have I&D with modular implant exchange. Patients were separated into three cohorts based on time from index procedure (≤4, 4–8, and ≥8 weeks), and were subsequently linked to treatment success and failure. Success was defined as the eradication of infection and resolution of presenting symptoms. All patients who required additional procedures due to infection were considered failures. Twenty-eight patients (73.7%) were successfully treated while 10 patients (26.3%) required further surgical interventions for persistent infection. Overall, average time between THA and I&D was 44.4 days. Successful I&Ds on average occurred within 41.9 days of the index procedure; while unsuccessful I&Ds were performed 51.6 days after index THA. Additionally, our study demonstrated that obese patients were more likely to fail debridement, antibiotics, irrigation, and retention of the prosthesis (DAIR) procedures (p = 0.006). While our results demonstrate that the average time to I&D with a modular exchange was shorter for those who had a successful outcome, the difference was not significant (p = 0.37).
Keywords: periprosthetic joint infection; irrigation and debridement; modular implant exchange; polyethylene liner exchange; total hip arthroplasty